Historical perspectives on costing of ODL courses: re-evaluate the implement at the Open University of Sri Lanka - Abeysinghe, A.M.P.B.; Jayatilleke, B.G.; Athapattu, Bandunee C L; Gamini, L.P.S. (Advances in Social Sciences Research Journal, 2016)
Many institutions in the world opted to use Open and Distance Learning (ODL) to get to the masses and to reach the unreached and empower them at an affordable cost. In view of this, the Open University of Sri Lanka (OUSL) was established in 1980as the dedicated ODL national university in Sri Lanka. As common anywhere in the world it was reported that the average cost per student in the OUSL is less than that of any conventional university in Sri Lanka on the basis of the average recurrent expenditure. Not strange, with rising educational costs in the country due to escalation of prices, offering study programmes at an affordable price while maintaining the quality is a challenge for OUSL. The OUSL is funded by government by means of salaries of its permanent staff, in recognition that it’s financial needs. In addition to that a course fee charged from enrolled student to cover other expenses of OUSL other than salaries. The course fee is charged from student is annually increased by ten per cent. In this context, re-examine costing of its courses may need to be correct urgently for rectifying anomaly and for updating with current changes. The OUSL to be established a formalised mechanism of costing its courses, in order to proceed with timely decisions to provide effective and efficient services to benefit stakeholders. Before establishing a formalised mechanism of costing its courses, it is worth to identify historical perspectives attempts of costing OUSL costing. Thus, this study attempts to historical perspectives on approaches practiced in determining costs of OUSL study programmes and thereby identify gaps in estimating costs and propose suggestions.